2010
DOI: 10.1590/s0103-50532010000800005
|View full text |Cite
|
Sign up to set email alerts
|

A simple synthesis of aminopyridines: use of amides as amine source

Abstract: A síntese de aminopiridinas foi realizada através de reações de formação de ligações C-N entre cloropiridina e uma variedade de amidas simples sob condições de refluxo, na ausência de metais de transição e irradiação por microondas (ou base).A transition metal/microwave irradiation (or base) free synthesis of aminopyridines has been accomplished via C-N bond forming reaction between chloropyridine and a variety of simple amides under refluxing conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Further evaluation showed that potassium tert-butoxide was the best base for this transformation because it afforded the desired product 2a in 85% yield (entry 7). Other solvents (DMSO, DCE, THF, 1,4-dioxane, toluene, and cyclohexane) were subsequently screened, and N,N-dimethylformamide proved to be the most efficient solvent (entries [8][9][10][11][12][13]. A control experiment showed that no reaction occurred without the addition of 4-toluenesulfonyl chloride (entry 14).…”
Section: Paper Syn Thesismentioning
confidence: 99%
See 4 more Smart Citations
“…Further evaluation showed that potassium tert-butoxide was the best base for this transformation because it afforded the desired product 2a in 85% yield (entry 7). Other solvents (DMSO, DCE, THF, 1,4-dioxane, toluene, and cyclohexane) were subsequently screened, and N,N-dimethylformamide proved to be the most efficient solvent (entries [8][9][10][11][12][13]. A control experiment showed that no reaction occurred without the addition of 4-toluenesulfonyl chloride (entry 14).…”
Section: Paper Syn Thesismentioning
confidence: 99%
“…The crude product was purified by chromatography (silica gel, PE-EtOAc, 15:1-10:1) to provide the corresponding product 2. 13 C NMR (100 MHz, CDCl 3 ): δ = 21. 6, 41.8, 115.0, 124.0, 125.5, 125.6, 128.2, 128.7, 128.9, 130.8, 137.8, 137.9, 153.0, 159.5, 163.9.…”
Section: -(Dimethylamino)quinazolines 2; General Proceduresmentioning
confidence: 99%
See 3 more Smart Citations